Bagaimanakah Aktivitas Belajar Siswa Sekolah Dasar Berlatar Belakang Keluarga Broken Home? - Maulid Farakh Anggita; Muhammad Abduh, M.Pd (Elementary Teacher Education Program, Majalengka University, 2023)
The family becomes the first and foremost place of learning for children. But not all families can be a comfortable place to learn for children, especially in broken homes. Many efforts have been made in improving the learning activities of children with broken home backgrounds, but there are still few that describe more deeply related to the learning activities of students from broken home families. The purpose of this study is to describe the learning activities of students with broken home family backgrounds in MI Ma'Arif Sraten. This research method uses a qualitative descriptive approach. Data collection techniques use interviews, observation and documentation. The data obtained were tested for the validity of the data by triangulation techniques, followed by data analysis with data reduction, data display and drawing conclusions. The results of the study showed that broken home family conditions had a negative influence on student learning activities. These influences include visul, oral, listening, writing, and mental activities, and there are impacts caused by broken home family conditions, namely the psychological condition of children who are disturbed and children's educational achievements that have decreased. It can be concluded that students' learning activities are influenced by broken home family conditions.